The John W* Knutson Distinguished Service Award in Dental Public Health - 2004 Recipient: Dr. Charles We Gish, DDS, MSD - Alice M. Horowitz, PhD (Blackwell Synergy, 2005)
Good Evening! And, welcome to the 23rd annual John W. Knutson Distinguished Service Award in Dental Public Health, sponsored by the Oral Health Section of the American Public Health Association.